Survival Comparisons of Hepatic Arterial Infusion Chemotherapy With mFOLFOX and Transarterial Chemoembolization in Patients With Unresectable Intrahepatic Cholangiocarcinoma - Cai, Zhiyuan; He, Chaobin; Zhao, Chongyu; Lin, Xiaojun (Frontiers in Oncology, 2021)
Background: Intrahepatic cholangiocarcinoma (ICC) has a poor prognosis and 40%-60% of patients present with advanced disease at the time of diagnosis. Transarterial chemoembolization (TACE) and hepatic arterial infusion chemotherapy (HAIC) have recently been used in unresectable ICC. The aim of this study was to compare the survival differences of unresectable ICC patients after TACE and HAIC treatment. Methods: Between March 2011 and October 2019, a total of 126 patients with unresectable ICC, as evident from biopsies and imaging, and who had received TACE or HAIC were enrolled in this study. Baseline characteristics and survival differences were compared between the TACE and HAIC treatment groups. Results: ICC Patients had significantly higher survival rates after the HAIC treatment, compared with those after TACE treatment [1-year overall survival (OS) rates: 60.2% vs 42.9%, 2-year OS rates: 38.7% vs 29.4%, P=0.028; 1-year progression-free survival (PFS) rates: 15.0% vs 20.0%, 2-year PFS rates: 0% vs 0%, P=0.641; 1-year only intrahepatic PFS (OIPFS) rates: 35.0% vs 24.4%, 2-year OIPFS rates: 13.1% vs 14.6%, P = 0.026]. Multivariate Cox regression analysis showed that HAIC was a significant and independent factor for OS and OIPFS in the study cohort. Conclusions: HAIC is superior to TACE for treatment of unresectable ICC. A new tumor response evaluation procedure for HAIC treatment in unresectable ICC patients is needed to provide better therapeutic strategies. A randomized clinical trial comparing the survival benefits of HAIC and TACE is therefore being considered.